Enriching the Teaching of Biology with Mathematical Concepts - Andersen, Janet (The American biology teacher, 2007)
Secondary school educators are told to teach more mathematics and science to their students to help them become more proficient in the two subjects. Coordination of mathematics and science teaching is recognized as another means of improving proficiency. The National Science Foundation has funded the "Mathematics, Science and Technology Partnership" at Hofstra University and Stony Brook University to enhance mathematical proficiency of middle school students through coordinated teaching of mathematics, science, and technology. Involvement in this project has inspired the author to incorporate mathematical concepts in her own college classroom. In particular, she used mathematical concepts to enhance the teaching of a biological course in Molecular Immunology, the study of the immune system. This course is taught to undergraduates and to perspective biology teachers at Stony Brook University. Three areas in the course have become enriched through the introduction of mathematical concepts. These areas are also covered briefly in other biology courses such as Molecular and Cellular Biology, Microbiology, and in various laboratory courses at Stony Brook University. The incorporation of mathematical concepts in these three areas is described in this article. The author has found that using mathematical concepts to enhance the teaching of immunology has enriched students' grasp of the subject and makes teaching more rewarding. (Contains 6 figures and 2 tables.)